The Model of Teacher Empowerment at the Level of the Islamic Revolution: a Meta-composite Study - Nayere Rahmani (علوم تربیتی از دیدگاه اسلام)
The current research was studied and carried out with the aim of designing a teacher empowerment model at the level of the Islamic Revolution. The method used in this research was data-based in terms of meta-composite approach and in terms of research strategy. The research community was a collection of articles related to the teacher, which were done with the Islamic approach, the menus of the Supreme Leader and other thinkers, and the document on the fundamental transformation of education since 1990. The theoretical sampling method was carried out and 38 studies were collected around this concept, the validity of the journals was also evaluated by being indexed in the database (WOS) and having a high impact factor, and they were analyzed with the coding technique of Strauss and Corbin. In the findings of the research, the central category "Empowering the teacher at the level of the revolution" was identified with 3 components of commitment, expertise and belonging. Taking into account the causal, contextual, intervening conditions and empowerment strategies, finally the result of empowerment was to introduce a wise teacher who, through revealed rationality, does things from mastery and strength, and with a preventive and growth-oriented approach, seeks to design programs in addition to strength. They have flexibility to some extent and provide the ground for the existential excellence of more teachers.